Experimental Performance Analysis of a Solar Desalination System Modified with Natural Dolomite Powder Integrated Latent Heat Thermal Storage Unit - Selimefendigil, Fatih; Sirin, Ceylin; Öztop, Hakan Fehmi (Mdpi, 2022)
Solar desalination systems are effective and sustainable applications that are utilized to obtain potable water from saline or contaminated water. In this research, three solar desalination systems, including a conventional system, a phase change material (PCM)-based thermal energy storage unit (TESU), and a natural dolomite powder integrated PCM-based TESU, were structured and experimentally investigated. The developed solar desalination systems were analyzed simultaneously and the findings were discussed in detail. According to the empirically obtained outcomes, utilizing PCM-based TESUs and dolomite-powder-embedded PCM-based TESUs increased daily cumulative productivity by 10.15% and 17.70%, respectively, in comparison to the conventional distiller. Employing dolomite powder increased the energy and exergy efficiencies of the conventional distiller from 15.91% to 18.28% and from 1.26% to 1.78%, respectively. Moreover, environmental metrics such as global warming potential and the sustainability index of the developed solar desalination systems were analyzed within the scope of this work.
Keywords: solar desalination system; dolomite; paraffin; thermal energy storage; energy-exergy